Microneedle-Based Electrochemical Devices for Transdermal Biosensing: A Review - Tasca-Gottardo, F; Tasca-Gottardo, F (Elsevier B.V., 2019)
Many research efforts over the last decade have been devoted to the development of microneedle-based diagnostic devices for minimally invasive transdermal biosensing and for long-term health monitoring. Transdermal biosensing via microneedle allows the development of minimally invasive easy-to-use point-of-care biodevices. The main objective of this short review is to provide a general overview of the most immediate and relevant progress in microneedle-based transdermal biosensing in the last five years. A critical analysis of the recent literature is finally presented. © 2019 Elsevier B.V.